2018
DOI: 10.1096/fasebj.2018.32.1_supplement.785.5
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Microtubules Blocks Axonal Mitochondrial Transport in a Human Pluripotent Stem Cell Model of Parkinson's Disease

Abstract: IntroductionNeuronal loss in Parkinson's disease (PD) is associated with both accumulation of aggregated α‐synuclein (α‐syn) and impaired mitochondrial function in dopaminergic neurons of the substantia nigra. These impairments are closely associated with the accumulation of reactive nitrogen species (RNS) such as nitric oxide and peroxynitrite. Moreover, exposure to mitochondrial toxins, such as the agrochemicals paraquat, maneb and rotenone, are associated with at least a 2.5‐fold increased risk of PD. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Accordingly, a previous study suggested that 3-NT reattributes cytoplasmic dynein in A549 epithelial cells by altering microtubule association (Eiserich et al, 1999). A more recent study revealed that DA neurons with a mutation in α-synuclein, exposed to agrochemicals, resulted in the inhibition of anterograde mitochondrial transport, thought to be mediated by the nitration of α-tubulins inhibiting the association of Kif5B, the heavy chain of kinesin-1, to microtubules (Stykel et al, 2018).…”
Section: The Effect Of 3-nt On the Axonal Transport Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a previous study suggested that 3-NT reattributes cytoplasmic dynein in A549 epithelial cells by altering microtubule association (Eiserich et al, 1999). A more recent study revealed that DA neurons with a mutation in α-synuclein, exposed to agrochemicals, resulted in the inhibition of anterograde mitochondrial transport, thought to be mediated by the nitration of α-tubulins inhibiting the association of Kif5B, the heavy chain of kinesin-1, to microtubules (Stykel et al, 2018).…”
Section: The Effect Of 3-nt On the Axonal Transport Machinerymentioning
confidence: 99%
“…Hence, the incorporation of 3-NT into αtubulin may disrupt these processes across different neuron types. Indeed, a recent study demonstrated that exposure to agrochemicals inhibits axonal transport of mitochondria in dopaminergic neurons carrying mutations associated with Parkinson's disease in the α-synuclein gene, possibly mediated by α-tubulin nitration (Stykel et al, 2018). However, whether 3-NT disrupts the regulation of axonal morphology in both dopaminergic and non-dopaminergic neurons remains to be determined.…”
Section: Introductionmentioning
confidence: 99%